Sweetie, you won't believe it [videorecording (DVD)] - Aibassov, Zhandos; Nurgaliyev, Yernar; Alshinov, Daniyar; Kalieva, Asel; Marklenov, Azamat (Trinity Creative Partnership, 2024)
A fishing trip with the boys quickly spirals out of control after witnessing a mob hit in the forest, setting off a series of insane, violent and hilarious misadventures. What begins with a couple quarreling about baby names soon ends in gory revenge and slapstick splatter in a seemingly indestructible one-eyed psychopath's cabin in the woods.